ELECTRODE FOR ELECTRICITY STORAGE DEVICE AND METHOD FOR MANUFACTURING SAME

JP7609432B2Active Publication Date: 2025-01-07I&T NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021190242
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-24
Publication Date
2025-01-07
Estimated Expiration
2036-12-22

AI Technical Summary

Benefits of technology

【0026】 本発明によれば、蓄電デバイスの充放電速度を向上することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609432000001
    Figure 0007609432000001
  • Figure 0007609432000002
    Figure 0007609432000002
  • Figure 0007609432000003
    Figure 0007609432000003
Patent Text Reader

Abstract

Provided are an electrode for an electricity storage device that can improve the charge / discharge rate of the electricity storage device, and a method for manufacturing the same. [Solution] The method for manufacturing an electrode for this energy storage device includes a slurry preparation step for preparing a liquid or gel-like slurry containing aluminum or copper short fibers A, an adsorbent material powder that adsorbs electrolyte ions during charging or an active material powder 20 that chemically reacts during charging and discharging, and a binder B; a forming step for forming the slurry into a predetermined shape; and a drying step for drying the slurry formed into the predetermined shape to form an electrode in which the aluminum or copper short fibers A function as a current collector.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode for an electricity storage device such as a secondary battery or a capacitor, and a method for manufacturing the same. [Background technology]

[0002] Capacitors and secondary batteries are used in a variety of fields for the purposes of reducing energy consumption and preventing global warming. In particular, the adoption of electrical energy in the automotive industry has accelerated the development of technologies that utilize these devices. Electric double layer capacitors have conventionally been used for backing up memories in electronic circuits to which low voltages are applied, and have higher input / output reliability than secondary batteries.

[0003] For this reason, in recent years, they have been used for generating electricity from natural energy sources such as solar and wind power, for construction machinery, for power supplies during momentary sags, and for regenerative power supplies in trains. Applications in automobiles have also been considered, but the characteristics and costs did not meet the requirements, and their use in this field was not realized until recently. However, electric double layer capacitors are now being used in electronically controlled brake systems, and applications such as backup power sources for automotive electrical equipment, starting energy supply for idling stop systems, brake control, and power assist are being considered.

[0004] The structure of an electric double layer capacitor is composed of positive and negative electrodes, an electrolyte, and a separator that prevents short-circuiting between the opposing positive and negative electrodes. The electrodes are formed by applying multiple layers of a mixture of polarizable electrodes (currently mainly activated carbon), a binder to hold the activated carbon, and a conductive assistant (mainly fine carbon particles) onto an aluminum foil (approximately 20 μm thick) that serves as a current collector. Such an electric double layer capacitor is disclosed in Patent Document 1, for example.

[0005] Electric double layer capacitors are charged by electrolyte ions moving through the solution and being adsorbed and desorbed on the microporous surface of the activated carbon. An electric double layer is formed at the interface between the activated carbon powder and the electrolyte. For reference, the particle size of normal activated carbon is, for example, about 4 to 8 μm, and the specific surface area is, for example, 1600 to 2500 m. 3 The electrolyte contains cations, anions, and a solvent, with tetraethylammonium salts used as cations, tetrafluoroborate ions used as anions, and propylene carbonate, ethylene carbonate, or the like used as the solvent.

[0006] On the other hand, a lithium ion secondary battery is mainly composed of a positive electrode, a negative electrode, and a separator. For example, as shown in Fig. 8, the positive electrode is generally a current collector made of aluminum foil having a thickness of 20 μm, which is coated with an active material powder, usually lithium cobalt oxide, a conductive additive, and a binder, to a thickness of about 100 μm, and the negative electrode is a current collector made of copper foil coated with a carbon material. These are separated by a separator such as polyethylene and immersed in an electrolyte to form a lithium ion secondary battery. Such a lithium ion secondary battery is disclosed in Patent Document 2, for example.

[0007] Charging and discharging are performed by the movement of lithium ions between the positive and negative electrodes. When charging, lithium ions move from the positive electrode to the negative electrode, and charging is completed when the positive electrode runs out of lithium ions or the negative electrode can no longer store lithium ions. When discharging, the opposite happens. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2005-086113 A [Patent Document 2] JP 2007-123156 A Summary of the Invention [Problem to be solved by the invention]

[0009] In recent years, the development of capacitors for power devices such as electric vehicles and energy generation has been progressing. In order to efficiently transfer large amounts of energy to and from a capacitor, it is necessary to increase the capacitance and reduce the internal resistance of the electrodes. A simple method would be to shorten the distance between the activated carbon and the aluminum member that serves as the current collector, and to place as much activated carbon as possible.

[0010] In general, electric double layer capacitors differ from secondary batteries, mainly lithium-ion secondary batteries, in that they do not involve chemical reactions, lose charge over time due to self-discharge, have a short storage time, and have a short current discharge time. Also, in terms of energy density, electric double layer capacitors have a few dozen Wh / L, compared to several hundred Wh / L for lithium batteries. It is due to the above differences that electric double layer capacitors are being considered for use not only for storing electricity, but also as backup power sources for electrical equipment, starting energy for idling stop systems, brake control, power assist, and so on.

[0011] Secondary batteries, mainly lithium batteries, have a relatively high energy density and can be used for a long time, so they are used in various fields including portable devices, and in recent years have begun to be used in automobiles, heavy machinery, energy fields, etc. However, there are still many issues with performance (capacity, charge / discharge speed, lifespan) and manufacturing costs, and these issues are particularly prominent in large batteries such as those used in automobiles. For example, the current used in a mobile phone is several mA, while the current used in a hybrid car is several hundred A, a difference between the two being more than 10,000 times. Therefore, it is necessary to increase the size of the battery to increase the capacity, but there are many issues with increasing the size, including capacity, charging speed, reliability, and manufacturing difficulties.

[0012] The reaction of lithium-ion secondary batteries is a reversible chemical reaction, and when the electrodes are charged and discharged, the volume of the active material expands and contracts. This causes the active material to peel off from the current collector, deteriorating the charge and discharge characteristics. In other words, the battery does not always charge and discharge at the same rate 100%, and the charge and discharge capacity decreases. In hybrid and electric vehicles, batteries are used for many years, so it is necessary to suppress the peeling of the active material from the current collector to prevent the above deterioration.

[0013] The biggest issue with lithium-ion batteries is their internal resistance, which is the resistance that lithium ions experience when moving through the electrolyte at the positive and negative electrodes inside the battery. This resistance to movement is the main reason why the capacity cannot be increased or the charge / discharge speed cannot be increased. When more active material is applied to the current collector to increase size, the capacity increases, but the resistance to movement also increases. For this reason, there is currently a limit to how thick the material can be. In addition, this resistance slows down the charge and discharge speed. If the thickness of the coating is made thinner, the internal resistance decreases and the charge and discharge speed increases, but the capacity decreases. For this reason, it becomes necessary to stack multiple current collectors coated with active material, or to increase the area of ​​the current collectors coated with active material.

[0014] The speed of charging and discharging also depends on the amount of lithium ions generated. If more ions can be produced and moved at once, the charging and discharging speeds will be faster. Since the chemical reaction in a secondary battery occurs at the interface with the electrolyte, increasing the contact area between the electrode and the electrolyte will also improve the charging and discharging speeds.

[0015] In order to reduce the internal resistance, improvements have been made to additives, conductive additives and active materials, and the current collector has been coated with fine carbon particles in advance. As for the shape of the current collector, improvements have been made to make it as thin as possible, as mentioned above, and to increase the surface area by forming fine holes in the foil. Similarly, research and development is being carried out for electric double layer capacitors, such as improving activated carbon and additives and increasing the contact area with the current collector.

[0016] As described above, in the field of secondary batteries such as electric double layer capacitors and lithium ion secondary batteries, which are electricity storage devices, efforts are being made to increase capacity, increase output, extend life, and reduce costs for use in electric vehicles, hybrid vehicles, and high-power energy devices.

[0017] The present invention has been made in view of the above circumstances, and has an object to provide an electrode for an electricity storage device that can improve the charge / discharge rate of the electricity storage device, and a method for manufacturing the same. [Means for solving the problem]

[0018] In order to solve the above problems, the present invention employs the following means. The method for producing an electrode for an electricity storage device according to the first aspect of the present invention includes dissolving a liquid or gel-like slurry containing aluminum or copper short fibers, an adsorbent powder to which electrolyte ions are adsorbed during charging or an active material powder that undergoes a chemical reaction during charging and discharging, and a binder. Fabrication Slurry Fabrication the step of forming the slurry into a predetermined shape; and the step of drying the slurry formed into the predetermined shape to form an electrode in which the aluminum or copper short fibers function as a current collector.

[0019] In this embodiment, when the slurry formed into a predetermined shape is dried, the aluminum or copper short fibers are electrically connected to each other, and a nonwoven current collector or a current collector in which the dispersed short fibers are connected to each other is formed by the short fibers. In addition, since the short fibers and the adsorbent powder or active material powder are mixed in the slurry, when the slurry is dried, the adsorbent powder or active material powder enters the gaps formed between the short fibers of the current collector. Therefore, the adsorbent powder or active material powder is in direct contact with the short fibers or is arranged in the vicinity of the short fibers, and the transfer resistance can be reduced when electrons are exchanged between the adsorbent powder or active material powder and the aluminum or copper short fibers.

[0020] The slurry of the above embodiment Fabrication In the step, the slurry containing the aluminum or copper short fibers, the adsorbent powder or the active material powder, the binder, and carbon fibers having an average thickness of 0.5 μm or less is Fabrication It is also possible to do so. In this case, when an electrode is formed, even if the adsorbent or active material powder and the short fibers are not in direct contact with each other, the adsorbent or active material powder and the short fibers are electrically connected via the carbon fibers. Also, even if the adsorbent or active material powder and the short fibers are in direct contact with each other, the electrical resistance between the adsorbent or active material powder and the short fibers is further reduced due to the connection through the carbon fibers.

[0021] In the above embodiment, it is also possible to further perform pre-drying before the forming step, in which the slurry is dried to a state in which the binder is not completely cured. In this case, the slurry before the forming step can be easily formed, which is advantageous in terms of improving the quality of the produced electrode and reducing the production cost.

[0022] An electrode for an electricity storage device according to a second aspect of the present invention comprises a current collector made of aluminum or copper short fibers having an average length of 25 mm or less, and an adsorbent powder that adsorbs electrolyte ions during charging or an active material powder that chemically reacts during charging and discharging, the active material powder filling gaps formed between the aluminum or copper short fibers of the current collector.

[0023] In this embodiment, the adsorbent powder or active material powder fills the gaps formed between the short fibers of the current collector, so that the adsorbent powder or active material powder is in direct contact with the short fibers or is arranged in the vicinity of the short fibers, thereby reducing the resistance to electron transfer when electrons are exchanged between the adsorbent powder or active material powder and each of the aluminum or copper short fibers.

[0024] In the above aspect, the current collector may further include carbon fibers having an average thickness of 0.5 μm or less that are inserted into gaps in the current collector. In this case, even if the adsorbent or active material powder is not in direct contact with the short fibers, the adsorbent or active material powder and the short fibers are electrically connected via the carbon fibers. Also, even if the adsorbent or active material powder and the short fibers are in direct contact with each other, the connection through the carbon fibers further reduces the electrical resistance between the adsorbent or active material powder and the short fibers.

[0025] In the above embodiment, the current collector may have at least one portion where two of the aluminum or copper short fibers are in contact so as to cross, and the two aluminum or copper fibers may bite into each other at the crossing portion. In this case, the resistance to electron movement at the contact points between the short fibers can be reduced, which is advantageous in reducing the resistance with which electrons move to the input / output terminals. In the above aspect, it is preferable that the aluminum used has a purity of 99.9% or more. In addition, a manufacturing method for an electrode for an electricity storage device of another embodiment of the present invention includes a slurry preparation step of preparing a liquid or gel-like slurry containing at least aluminum or copper short fibers, an adsorbent material powder that adsorbs electrolyte ions during charging or an active material powder that chemically reacts during charging and discharging, a conductive assistant, a binder, and carbon fibers having an average thickness of 0.5 μm or less, a molding step of forming the slurry into a predetermined shape, and a drying step of drying the slurry formed into the predetermined shape to form an electrode, wherein the average length of the short fibers is 25 mm or less. In addition, an electrode for an electricity storage device according to another embodiment of the present invention comprises short aluminum or copper fibers having an average length of 15 mm or less, an adsorbent powder that adsorbs electrolyte ions during charging or an active material powder that undergoes a chemical reaction during charging and discharging, which fills gaps formed between the short aluminum or copper fibers, a conductive assistant, and carbon fibers having an average thickness of 0.5 μm or less. In addition, a manufacturing method for a capacitor electrode according to another embodiment of the present invention includes a slurry preparation step of preparing a liquid or gel-like slurry containing at least aluminum or copper short fibers, an adsorbent powder that adsorbs electrolyte ions during charging, and a binder, a forming step of forming the slurry into a predetermined shape, and a drying step of drying the slurry formed into the predetermined shape to form an electrode, wherein the average length of the short fibers is 15 mm or less. In addition, a capacitor electrode according to another embodiment of the present invention comprises aluminum or copper short fibers having an average length of 25 mm or less, an adsorbent powder that fills gaps formed between the aluminum or copper short fibers and adsorbs electrolyte ions during charging, a conductive additive, and carbon fibers having an average thickness of 0.5 μm or less. Effect of the Invention

[0026] According to the present invention, the charge / discharge rate of an electricity storage device can be improved. [Brief description of the drawings]

[0027] [Figure 1] FIG. 2 is a cross-sectional image diagram of an electrode according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a method for producing a slurry according to the present embodiment. [Diagram 3] FIG. 2 is a schematic diagram of a method for forming the slurry of the present embodiment into a predetermined shape. [Figure 4] 4 is a schematic diagram of another method for forming the slurry of the present embodiment into a predetermined shape. FIG. [Diagram 5] FIG. 4 is a cross-sectional image diagram of an electrode according to a first modified example of the present embodiment. [Figure 6] FIG. 11 is a cross-sectional image diagram of an electrode according to a second modified example of the present embodiment. [Figure 7] FIG. 1 is a cross-sectional view of a coin-type secondary battery using the electrode of the present embodiment. [Figure 8] FIG. 1 is a cross-sectional view of a conventional coin-type secondary battery. [Figure 9]FIG. 1 is a cross-sectional view of an electric double layer capacitor using the electrode of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] An electrode according to one embodiment of the present invention will be described below with reference to the drawings. As shown in FIG. 1, this electrode comprises a current collector 10 in the form of a nonwoven fabric made of aluminum or copper short fibers A having an average wire diameter of 100 μm or less, or in which the short fibers A are arranged so as to be in contact with each other, and active material powder 20 that is held by binder B on the current collector 10 and undergoes a chemical reaction during charging and discharging, and, if necessary, a conductive assistant 30 held by binder B on the current collector 10.

[0029] 1 is a diagram for easily understanding the configuration of this embodiment, and the sizes, thicknesses, lengths, etc. of the short fibers A, active material powder 20, conductive assistant 30, carbon fibers CF, etc. may differ from the actual sizes, thicknesses, lengths, etc. In addition, in FIG. 1, it is also possible to hold an adsorbent powder that adsorbs electrolyte ions during charging on the current collector 10, instead of the active material powder 20.

[0030] [Forming short aluminum fibers to serve as current collectors] The aluminum or copper short fibers A have, for example, an average length of 25 mm or less, preferably 20 mm or less, more preferably 15 mm or less, and an average wire diameter of 50 μm or less, preferably 25 μm or less. The aluminum or copper short fibers A are formed, for example, by a chatter vibration cutting method in which a cutting tool is applied to a columnar aluminum or copper member having a circular cross section, or by a milling cutting method. It is also possible to form aluminum or copper short fibers having the above wire diameter and length by other methods.

[0031] [Electrode formation] First, a liquid or gel-like slurry S containing aluminum or copper short fibers A, active material powder 20 that chemically reacts during charging and discharging, a conductive assistant 30, and a binder B is mixed. FabricationThe slurry S is prepared by kneading a mixture of aluminum or copper short fibers A, active material powder 20, conductive additive 30, and diluted binder B. Fabrication Since the aluminum or copper short fibers A have an average length of 25 mm or less, the aluminum or copper short fibers A, the active material powder 20, and the conductive assistant 30 are easily mixed in the slurry S. When the average length of the short fibers A is 15 mm or less, they tend to be more easily mixed.

[0032] Next, pre-drying is performed to increase the viscosity of the slurry S. Pre-drying is performed to dry the binder B to a state where it is not completely hardened, thereby making it easier to mold the slurry S into a predetermined shape, and therefore may be omitted depending on the viscosity of the binder B. Next, as shown in Fig. 3, the slurry S is placed in a mold and pressurized. This allows the slurry S to be molded to a predetermined thickness according to the size of the electrode. As shown in Fig. 4, the slurry S can also be pressurized by passing the slurry S between a pair of rollers, thereby molding the slurry S to a predetermined thickness according to the size of the electrode. After adjusting the thickness of the slurry S with a mold or rollers, the slurry S can also be cut and molded into a predetermined shape (size).

[0033] Next, a drying step is performed in which the molded slurry S is dried by vacuum drying or the like. This hardens the binder B in the slurry S, and the active material powder 20 and the conductive assistant 30 in the slurry S are held by the short fibers A of the current collector 10 by the binder B. Depending on the amount of short fibers A in the slurry S, after drying the slurry S, the short fibers A may be dispersed in the dried slurry S and the short fibers A arranged adjacent to each other may come into direct contact with each other, or the short fibers A arranged adjacent to each other may be electrically connected via the active material powder 20 or the conductive assistant 30, and the current collector 10 may be formed by the short fibers A dispersed in the slurry S. Even in this case, at least a part of the active material powder 20 and the conductive assistant 30 in the slurry S is held by the short fibers A.

[0034] It is also possible to carry out a pressurizing step of pressing the current collector 10 after the drying step. The pressurizing step can include a step of passing the current collector 10 between a pair of rollers, a step of sandwiching the current collector 10 between a pair of flat surfaces, a step of pressing the current collector 10 using a mold, or the like.

[0035] By using aluminum or copper, particularly preferably aluminum with a purity of 99.9% or more, and more preferably aluminum with a purity of 99.99% or more, when pressing as shown in Fig. 3 or 4 or pressing the current collector 10 after the drying step, it is possible to adjust the pressure so that the two intersecting end fibers A are deformed so as to bite into each other at the contact portions where the short fibers A cross each other. In other words, the short fibers A are flattened at the contact portions, and as a result, the two intersecting end fibers A appear to be biting into each other.

[0036] In this case, the resistance to electron movement at the contact points between the short fibers A can be reduced, which is advantageous in reducing the resistance with which electrons move to the input / output terminals. In addition, instead of the slurry S containing the active material powder 20, a slurry S containing an adsorbent powder to which electrolyte ions are adsorbed during charging is used. Fabrication In this case, the adsorbent powder is held in place of the active material powder 20 on the short fibers A of the current collector 10 after the drying step.

[0037] [Active material powder] The active material powder 20 may be any material that can be held by the current collector 10 with the binder B or the like, or that can be held by the binder B hardened together with the current collector 10, and is preferably one with excellent cycle characteristics. Examples of active materials include lithium cobalt oxide (LiCoO2), iron phosphate-based active materials, and carbon materials such as graphite. It is possible to use known active materials that are used for the positive and negative electrodes of secondary batteries.

[0038] [Adsorbent powder] The adsorbent powder used in place of the active material powder 20 may be any powder that can be held by the current collector 10 with the binder B or the like, or that can be held by the binder B hardened together with the current collector 10, and is preferably one that has excellent cycle characteristics. Examples of the adsorbent powder include polyacene (PAS), polyaniline (PAN), activated carbon, carbon black, graphite, carbon nanotubes, etc. It is possible to use known substances that are used for the positive and negative electrodes of electric double layer capacitors.

[0039] The active material powder 20 and the adsorbent powder are preferably pulverized using a mortar, ball mill, vibrating ball mill, or the like to reduce the average particle size to a predetermined value or less. The predetermined value may be the average linear diameter of the short fibers A of the current collector 10 plus 10 μm. For example, when the average linear diameter of the short fibers A is 20 μm, the active material powder 20 and the adsorbent powder preferably have an average particle size of 30 μm or less. This increases the contact area between the short fibers A of the current collector 10 and the active material powder 20 or the adsorbent powder, which can contribute to improving the charge and discharge rate.

[0040] [binder] Thermoplastic resins, polysaccharide polymer materials, etc. can be used as the binder B. Examples of binder materials include polyacrylic resins, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), copolymers of vinylidene fluoride (VdF) and hexafluoropropylene (HFP), etc. It is possible to use known binders used in electrodes of secondary batteries and electric double layer capacitors.

[0041] [Conductive additive] The conductive assistant 30 may be any material that has conductivity, and is preferably a material that does not undergo chemical changes due to electrolytes or solvents. Examples of the conductive assistant 30 include graphite and carbon black. It is possible to use known conductive assistants that are used in electrodes of secondary batteries and electric double layer capacitors.

[0042] The electrodes prepared as described above can be used as electrodes of electricity storage devices such as electric double layer capacitors, secondary batteries, and hybrid capacitors including lithium ion capacitors. For example, they can be used as the positive and negative electrodes of electric double layer capacitors, as an example of secondary batteries, they can be used as the positive and negative electrodes of lithium ion secondary batteries, and they can be used as the positive and negative electrodes of lithium ion capacitors. Examples of their applications will be described later.

[0043] It is also possible to use a slurry containing powder of carbon fibers CF having an average thickness of 0.5 μm or less, preferably 0.3 μm or less, in addition to the active material powder 20, the conductive assistant 30, and the binder B, as the slurry S. In this case, the carbon fibers CF are disposed in gaps formed in the current collector 10, as shown in FIG.

[0044] The carbon fibers CF are in contact with the short fibers A, the active material powder 20, the conductive assistant 30, and other carbon fibers CF. In this embodiment, carbon fibers CF having an average thickness of 0.1 to 0.2 μm and a length of about 20 to 200 μm are used. The resistivity of the carbon-based conductive assistant 30 is 0.1 to 0.3 Ω·cm, whereas the resistivity of the carbon fibers CF is, for example, 5×10 -5 Ω cm.

[0045] For example, even when the active material powder 20 and the short fibers A are not in direct contact with each other, the active material powder 20 and the short fibers A are electrically connected to each other via the carbon fibers CF. Even when the active material powder 20 and the short fibers A are in direct contact with each other, the electrical resistance between the active material powder 20 and the short fibers A is further reduced due to the connection by the carbon fibers CF. In this way, the carbon fibers CF having good electrical conductivity can reduce the resistance to the movement of electrons between the active material powder 20 and the short fibers A, which is advantageous in reducing the resistance with which electrons move to the input / output terminals.

[0046] It is also possible to manufacture an electrode using a slurry containing carbon fibers CF without the conductive assistant 30. In this case, too, as shown in Fig. 6, the carbon fibers CF are arranged in gaps formed in the current collector 10, and this configuration is advantageous in terms of reducing the electrical resistance between the active material powder 20 and the short fibers A. It is noted that Figs. 5 and 6 are diagrams for easily illustrating the configuration of this embodiment, and the size, thickness, and length of the short fibers A, active material powder 20, conductive assistant 30, carbon fibers CF, etc. may differ from the actual sizes, thicknesses, and lengths. In order to efficiently reduce electrical resistance, the average length of the carbon fibers CF is preferably at least half the average particle size of the active material powder 20 or the adsorbent powder, and more preferably at least 2 / 3 of the average particle size.

[0047] [Application to coin-type secondary batteries] 7 shows an example of a coin-type secondary battery using the electrode of this embodiment. This coin-type secondary battery includes a case (outer can) 100 having a case body 102 and a lid 101, and a power storage unit housed in the case 100. The power storage unit includes an electrode using the short fibers A made of aluminum of this embodiment as a positive electrode 110. It also includes a negative electrode 120 facing the positive electrode 110, and a separator 130 disposed between the positive electrode 110 and the negative electrode 120. The positive electrode 110 is in surface contact with the case body 102, and the negative electrode 120 is in surface contact with the lid 101, so that the lid 101 and the case body 102 function as input / output terminals for the positive electrode 110 and the negative electrode 120.

[0048] In this case, the current collector 10 used for the positive electrode 110 holds the active material powder 20 for the positive electrode. The negative electrode 120 may have the structure and material of a known negative electrode of a secondary battery, and in the case of a lithium ion secondary battery, a carbon material such as graphite is used as the active material, and a copper foil is used as the current collector. The separator 130 may be any material that electrically insulates the positive electrode 110 and the negative electrode 120, has ion permeability, and has resistance to oxidation and reduction at the contact surface with the positive electrode 110 and the negative electrode 120. For example, a porous polymer or inorganic material, an organic-inorganic hybrid material, glass fiber, etc. may be used. A known separator used in a secondary battery may be used.

[0049] The case 100 housing the power storage unit is filled with an electrolytic solution. Lithium salt, potassium salt, sodium salt, magnesium salt, etc. can be used as the electrolyte of the electrolytic solution, and lithium salt is used in the case of a lithium ion secondary battery. A non-aqueous solvent is used as the solvent in which the electrolyte dissolves, and ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, carbonate ester, etc. can be used as the non-aqueous solvent. It is possible to use known electrolytes and solvents used in secondary batteries. When charging and discharging are performed, a chemical reaction occurs in which ions such as lithium ions are released from the active material powder 20 of the positive electrode 110 into the electrolytic solution, and a chemical reaction occurs in which ions such as lithium ions are taken into the active material powder 20.

[0050] In the coin-type secondary battery thus configured, one surface in the thickness direction of the current collector 10 used for the positive electrode 110 contacts the case body 102. Moreover, the current collector 10 used for the positive electrode 110 is filled with active material powder 20 over the entire range from one surface to the other surface in the thickness direction, and most of the active material powder 20 contacts the short fibers A of the current collector 10. This reduces the distance between the short fibers A that carry electrons to the input / output terminals and the active material powder 20, which is advantageous in improving the charge / discharge speed.

[0051] Furthermore, the active material powder 20 and the short fibers A are in direct contact with each other, or the active material powder 20 and the short fibers A are arranged close to each other and are electrically connected via the conductive assistant 30, etc. Therefore, when electrons are exchanged between the active material powder 20 and the short fibers A, the resistance with which the electrons move to an input / output terminal provided at an end of the current collector 10, etc., can be reduced.

[0052] An example of a conventional coin-type secondary battery is shown in FIG. 8. This coin-type secondary battery includes a positive electrode 140 having an aluminum foil current collector 141 and an electrode layer 142 applied to one surface of the current collector 141 in the thickness direction. The electrode layer 142 contains active material powder, a conductive assistant, a binder, and the like. Since the coin-type secondary battery has a limited space, the amount of active material powder in the conventional coin-type secondary battery is limited by the thickness of the current collector 141. In addition, the electrons of the active material powder arranged on the separator 130 side move to the current collector 141 via the active material powder and conductive assistant arranged between the current collector 141 and the positive electrode 140, which is not preferable in terms of improving the charge / discharge speed.

[0053] In the coin-type secondary battery, it is also possible to use the electrode structure of this embodiment, particularly an electrode using short fibers A made of copper, for the negative electrode 120. In this case, the current collector of this electrode becomes the current collector 10, and a carbon material is used as the active material powder 20, and lithium titanate, titanium oxide, tungsten oxide, tin oxide, etc. may also be used depending on the type of battery.

[0054] [Application to stacked secondary batteries] In the case of a secondary battery in which a storage section consisting of a positive electrode, a negative electrode, and a separator is stacked in multiple layers, the electrode structure using the aluminum or copper short fibers A of this embodiment can be used for only the positive electrode, only the negative electrode, or both the positive electrode and the negative electrode, as in the coin-type secondary battery.

[0055] [Application to electric double layer capacitors] 9 shows an example of an electric double layer capacitor using the electrodes of this embodiment. This electric double layer capacitor includes, for example, a container 200 and a storage unit housed in the container 200. The storage unit includes an electrode using the aluminum short fibers A of this embodiment as a positive electrode 210. The storage unit also includes a negative electrode 220 facing the positive electrode 210, and a separator 230 disposed between the positive electrode 210 and the negative electrode 220. A positive electrode input / output terminal 210a is connected to the positive electrode 210, and a negative electrode input / output terminal 220a is similarly connected to the negative electrode 220, with each input / output terminal extending to the outside of the container 200.

[0056] In this case, the current collector 10 used for the positive electrode 210 holds an adsorbent powder. The negative electrode 220 may have the structure and material of a known negative electrode of an electric double layer capacitor, and includes, for example, a current collector 221 made of aluminum foil, and an electrode layer 222 applied to one surface of the current collector in the thickness direction. The electrode layer 222 contains an adsorbent powder, a conductive assistant, a binder, and the like.

[0057] The separator 230 may be any material that electrically insulates the positive electrode 210 and the negative electrode 220, has ion permeability, and has resistance to oxidation and reduction at the contact surface with the positive electrode 210 and the negative electrode 220. For example, it is possible to use porous polymers, inorganic materials, organic-inorganic hybrid materials, glass fibers, etc. It is also possible to use known separators used in electric double layer capacitors.

[0058] The container 200 housing the storage unit is filled with an electrolytic solution. The electrolytic solution contains a non-aqueous solvent and an electrolyte. The electrolyte and the non-aqueous solvent may be any known substance used in electric double layer capacitors. For example, ammonium salts, phosphonium salts, etc. can be used as the electrolyte, and for example, cyclic carbonate esters, chain carbonate esters, cyclic esters, chain esters, cyclic ethers, chain ethers, nitriles, sulfur-containing compounds, etc. can be used as the non-aqueous solvent.

[0059] In this electric double layer capacitor, one end of the current collector 10 used in the positive electrode 210 is connected to the positive electrode input / output terminal 210a. The current collector 10 used in the positive electrode 210 is filled with adsorbent powder over the entire range from one surface to the other surface in the thickness direction, and most of the adsorbent powder is in contact with the short fibers A of the current collector 10. This reduces the distance between the short fibers A that carry electrons to the positive electrode input / output terminal 210a and the adsorbent powder, which is advantageous in improving the charge / discharge rate. The structure of the conventional positive electrode is the same as that of the negative electrode 220, so the above advantages are easier to understand compared to the negative electrode 220. In the electric double layer capacitor, it is also possible to use an electrode structure in which the aluminum short fibers A of this embodiment are used for the negative electrode 220. It is also possible to use an electrode structure in which the copper short fibers A of this embodiment are used for the positive electrode 210 and the negative electrode 220.

[0060] According to this embodiment, as described above, it is possible to form an electrode for an electricity storage device in which the active material powder 20 or the adsorbent powder is disposed in the vicinity of the high-purity aluminum short fibers A or the copper short fibers A. This makes it possible to manufacture an electricity storage device with higher capacity, lower deformation resistance, and excellent charge / discharge properties.

[0061] For example, the aluminum foil used in ordinary capacitors and secondary batteries is manufactured by making a very large rectangular aluminum ingot called a slab, cutting, heating, rolling it many times, and further performing surface treatment. This requires a lot of energy and cost. On the other hand, the aluminum or copper short fiber A used in this embodiment can be manufactured by chatter vibration cutting or the like. In addition, when the current collector 10 holding the adsorbent powder, active material powder 20, conductive additive 30, etc. is rolled to form a foil, the pressing pressure can be reduced. Therefore, it is possible to easily manufacture the current collector foil and the positive electrode foil at low cost without requiring large-scale equipment.

[0062] Thus, according to this embodiment, when the slurry formed into a predetermined shape is dried, the aluminum or copper short fibers A are electrically connected to each other, and the aluminum or copper short fibers A form the current collector 10. Furthermore, since the aluminum or copper short fibers A and the adsorbent material powder or active material powder 20 are mixed in the slurry S, when the slurry S is dried, the adsorbent material powder or active material powder 20 enters into the gaps formed between the short fibers A of the current collector 10. For this reason, the adsorbent material powder or active material powder 20 is in direct contact with the short fibers A or is disposed in the vicinity of the short fibers A, and when electrons are exchanged between the adsorbent material powder or active material powder 20 and the short fibers A, the transfer resistance can be reduced.

[0063] Furthermore, because the carbon fibers CF are mixed into the slurry S, when the electrode is formed, even if the adsorbent powder or active material powder 20 is not in direct contact with the short fibers A, the adsorbent powder or active material powder 20 and the short fibers A are electrically connected via the carbon fibers CF. Even if the adsorbent powder or active material powder 20 and the short fibers A are in direct contact with each other, the electrical resistance between the adsorbent powder or active material powder 20 and the short fibers A is further reduced due to the connection by the carbon fibers CF.

[0064] Furthermore, electrodes having a nonwoven current collector made of short fiber A or a current collector in which dispersed short fiber A is connected to each other can be easily bent with a small force compared to those that use aluminum foil or the like as a current collector. Therefore, when the installation space for the electrode is limited, it is possible to facilitate its installation, and even when the electrode is installed in a position where it is subject to slight deformation during use, the reaction force generated by the electrode is small, which is expected to improve the life of the device. [Explanation of symbols]

[0065] 10 Current collector 20 Active material powder 30 Conductive assistant A Short aluminum or copper fiber B. Binder S Slurry CF Carbon Fiber

Claims

1. a slurry preparation step of preparing a liquid or gel-like slurry containing at least short aluminum or copper fibers, an adsorbent powder to which electrolyte ions are adsorbed during charging or an active material powder that undergoes a chemical reaction during charging and discharging, a conductive assistant, a binder, and carbon fibers having an average diameter of 0.5 μm or less; A forming step of forming the slurry into a predetermined shape; A method for manufacturing an electrode for an electricity storage device, comprising: a drying step of forming an electrode by drying the slurry formed into the predetermined shape, The method for producing an electrode for an electricity storage device, wherein the short fibers have an average length of 25 mm or less.

2. The method for manufacturing an electrode according to claim 1 , wherein the short fibers are made of aluminum having a purity of 99.9% or more.

3. Short aluminum or copper fibers having an average length of 15 mm or less; An electrode for an electricity storage device comprising: an adsorbent powder that adsorbs electrolyte ions during charging or an active material powder that undergoes a chemical reaction during charging and discharging, the active material powder filling gaps formed between the aluminum or copper short fibers; at least one of fine carbon particles, carbon black, and graphite particles; and carbon fibers having an average thickness of 0.5 μm or less.

4. The short fibers are made of aluminum having a purity of 99.9% or more, The electrode according to claim 3 , wherein the electrode has at least one portion where two of the short fibers are in contact with each other so as to cross each other, and the two short fibers are embedded in each other at the crossing portion.

5. a slurry preparation step of preparing a liquid or gel-like slurry containing at least aluminum or copper short fibers, an adsorbent powder to which electrolyte ions are adsorbed during charging, a binder, and at least one of fine carbon particles, carbon black, and graphite particles; A forming step of forming the slurry into a predetermined shape; and drying the slurry formed into the predetermined shape to form an electrode, The method for manufacturing a capacitor electrode, wherein the short fibers have an average length of 15 mm or less.

6. Short aluminum or copper fibers having an average length of 25 mm or less; A capacitor electrode comprising: an adsorbent powder that fills the gaps formed between the aluminum or copper short fibers and adsorbs electrolyte ions during charging; a conductive assistant; and carbon fibers having an average thickness of 0.5 μm or less.

Citation Information

Patent Citations

  • Electric double layer capacitor

    JP2005086113A

  • Lithium ion cell

    JP2007123156A

  • Lithium ion secondary battery

    JP2011154955A

  • Positive electrode for lithium ion secondary battery and method of manufacturing the same

    JP2014191919A